Identifikasi Kemampuan Berpikir Logis Dalam Pemecahan Masalah Matematika Pada Siswa Kelas XI SMAN 6 Madiun - Sukma Choirun Nisa; Edy Suprapto; Eka Sari (Journal on Education, 2024)
Mathematics is seen as learning material needed to solve problems in life. Learning mathematics can improve students' ability to think logically. Logical thinking means a child's ability to think rationally, by utilizing logical abilities, so that they can think logically. This type of research is descriptive qualitative. This research to describe the ability to think logically in solving mathematical problems in high school students. The subjects of this research were three students, namely students with high, medium and low problem solving abilities from class XI-J of SMAN 6 Madiun for the 2023/2024 academic year. The research instrument consists of test questions and interview guidelines. The results of research show that in solving mathematical problems: high ability subjects show the characteristics of logical thinking ability, able to think coherently, can provide arguments in each step of problem solving, able to provide appropriate conclusions; moderately capable subjects show characteristics of logical thinking ability, able to think coherently, able to provide arguments in each step of problem solving, able to provide conclusions but are not precise; Low ability subjects show characteristics of logical thinking ability, able to think coherently, unable to provide arguments in each step of problem solving, unable to provide conclusions.